Cash Waqf Linked Sukuk: Strategi Penguatan Ekosistem Wakaf Produktif Di Indonesia - Santi Arafah; Yunanda Eka Putra; Yenni Samri Juliati Nasution; Marliyah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2025)
This research aims to determine strategies for strengthening the productive waqf ecosystem in Indonesia. This study is qualitative in nature with a library research approach, meaning that the data used in this study is sourced from various books, journals, dictionaries, encyclopedias, and other documents related to the object of this study. Data analysis includes activities such as categorizing data, organizing data, manipulating data, and summarizing data to obtain answers to the research questions. The methods used to analyze the data in this study are deductive and comparative methods. The results of this study explain that cash waqf linked sukuk is a strategy to strengthen the productive waqf ecosystem in Indonesia. Cash waqf linked sukuk has several objectives, including facilitating waqif to be able to donate money more easily and safely, supporting the development of the Islamic financial market, particularly the cash waqf industry, encouraging the diversification of Islamic banking businesses through the optimization of the role of LKS PWU, and encouraging the development of the national waqf ecosystem, particularly strengthening the governance and institutions of national waqf